Reforma de la Constitución Explicada por miembros de la Comisión de Redacción - ROSATTI, Horacio (RUBINZAL-CULZONI, 1994)
Otros autores: BARRA, Rodolfo C.; GARCIA LEMA, Alberto M.; MASNATTA, Héctor; PAIXAO, Enrique; QUIRIGA LAVIE, Humberto. Colaboración: MOSSET ITURRASPE, Jorge